MAPPING THE POTENTIAL CO2 SOURCE-SINKS FOR CARBON CAPTURE STORAGE FROM INDUSTRY IN INDONESIA - Muhammad Firdaus Al Hakim; Brian Tony; Steven Chandra; Fanata Y. Nugraha; Damar Nandiwardhana (Testing Center for Oil and Gas LEMIGAS, 2025)
The increasing trend of carbon reduction program in Indonesia has been intensified to achieve Net-Zero Emission in 2060. One of the option to achieve this commitment is by implement Carbon Capture and Storage (CCS) program in Indonesia as this technology offers reducing carbon dioxide (CO2) by taking the CO2 directly from the emitter and safely inject it to the depleted reservoir. This study aims to map the potential of CCS Storage from oil and gas depleted reservoir as the candidates of sink and its connectivity with the available CO2 Source from Cement, Petrochemical, and Fertilizer industry. The depleted oil and gas reservoir storage capacity is calculated from the available data of oil and gas in place with its ultimate recovery. The pipeline right of ways is also mapped to evaluate the connectivity of the CO2 emitter and CO2 storage. There are four major region which could potentially developed for further CCS impelementation program. The South Sumatera Region holds 3 MtCO2 annual emission from the industry and connected to surrounding storage via pipeline with total capacity of 584 MtCO2. Both West Java and East Java hold advantages for CCS as the West Java available storage 612 MtCO2 while East Java 345 MtCO2 while the annual emission from industry in West Java and East Java are 13 MtCO2 and 9 MtCO2 respectively. In Kalimantan, there are potency of 15 MtCO2 annual emission with 1,945 MtCO2 storage capacity.